EFL learners’ perception of the project-based learning method in extensive reading course - Harini (English Language Education Study Program, Faculty of Education and Teacher Training, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, Indonesia, 2021)
The lack of English reading ability in Indonesian students is a common problem, and many times the teacher uses the Project-Based Learning (PBL) method to help students improve their English reading ability. This study wants to portray students’ perception of the PBL method in the English extensive reading course. Data of this study were collected through interviews. The participants of this research involved five students from the English Extensive Reading class. The data were analyzed using Miles and Huberman analysis technique. By using a narrative inquiry, this study found that, according to the students' perception, the teacher provides projects that aim to support understanding of the material that has been given to students. In that activity, the teacher has a role as a facilitator. She guides the students to do the project and provides feedback to them. However, in the process of implementing PBL, the students find it difficult in terms of time because the project takes a long time. Overall, PBL help students comprehend better in the English extensive reading course.